Acute and chronic health impacts of PM2.5 in China and the influence of interannual meteorological variability. (15th May 2020) - Wang, Yuanlin; Wild, Oliver; Chen, Huansheng; Gao, Meng; Wu, Qizhong; Qi, Yi; Chen, Xueshun; Wang, Zifa
Abstract: High concentrations of PM2.5 in China have an adverse impact on human health and present a major problem for air quality control. Here we evaluate premature deaths attributable to chronic and acute exposure to ambient PM2.5 at different scales in China over 2013–2017 with an air quality model at 5 km resolution and integrated exposure-response methods. We estimate that 1, 210, 000 (95% Confidence Interval: 720, 000–1, 750, 000) premature deaths annually are attributable to chronic exposure to PM2.5 pollution. Chongqing exhibits the largest chronic per capita mortality (1.4‰) among all provinces. A total of 116, 000 (64, 000–170, 000) deaths annually are attributable to acute exposure during pollution episodes over the period, with Hubei province showing the highest acute per capita mortality (0.15‰). We also find that in urban areas premature deaths are 520, 000 (320, 000–760, 000) due to chronic and 55, 000 (3, 000–81, 000) due to acute exposure, respectively. At a provincial level, the annual mean PM2.5 concentration varies by ±20% due to interannual variability in meteorology, and PM2.5 –attributable chronic mortality varies by ±8%, and by >±5% and ±1% at a national level. Meteorological variability shows larger impacts on interannual variations in acute risks than that in chronic exposure at both provincial (>±20%) and national (±4%) levels. These findings emphasize that tighter controls of PM2.5 and precursor emissions are urgently needed, particularly under unfavorable meteorological conditions in China. Highlights: High-resolution simulation is used to estimate chronic and acute premature deaths attributable to PM2.5 over China. 1, 210, 000 and 116, 000 premature deaths annually are attributable to chronic and acute exposure to PM2.5. In urban areas chronic and acute premature deaths are 520, 000 and 55, 000, respectively. Meteorology variability has larger impacts on interannual variations in chronic and acute exposure at provincial level.